Measurement of Lumbar Spine Functional Movement in Low Back Pain. Issue 10 (October 2015) - Vaisy, Morad; Gizzi, Leonardo; Petzke, Frank; Consmüller, Tobias; Pfingsten, Michael; Falla, Deborah
<x xml:space="preserve">Abstract</x> Objectives: Individuals with low back pain (LBP) present with alterations or limitations of spinal mobility. The identification of simple clinical methods for evaluating functional movement of the spine is necessary to allow quantification of the degree of movement impairment and permit monitoring of patient improvement with rehabilitation. This study evaluated movement of the spine in 20 patients with chronic nonspecific LBP compared with 19 pain-free participants using a novel measurement device that permits the dynamic assessment of spinal movement in a rapid and subject-specific manner. Methods: Two flexible sensor strips were fixed paravertebrally to the spine with each sensor strip measuring angles in 12 predetermined, adjacent, 25-mm-long segments. Maximum range of motion (ROM) and average angular velocity (AAV) of lumbar and pelvic movement were measured within identical angular and temporal frames during the descending and ascending phase of active lumbar flexion, extension, rotation, and lateral flexion following a standard choreography. Participants with LBP completed a number of questionnaires including the Tampa Scale of Kinesiophobia, Pain Catastrophizing Scale, and Spielberger State-Trait Anxiety Inventory. Results: Across all movements, the individuals with LBP displayed 10% to 15% less ROM (P<0.05) and 15% to 30% less AAV (P<0.05) at both the pelvis and lumbar regions compared with controls. ROM as well as AAV, in most cases, were negatively correlated (R=−0.49 to −0.75) with the Tampa Scale of Kinesiophobia, Pain Catastrophizing Scale, and Spielberger State-Trait Anxiety Inventory in the LBP group (all P<0.05) especially during the initial descending phase of movement. Discussion: This study provide support for the utility of this device for quantifying movement impairments in individuals with fairly low levels of LBP and general functional limitations. The results show that velocity measurements rather than ROM show the greatest differences in individuals with LBP compared with asymptomatic participants. Impaired lumbar and pelvis movement was correlated to the individuals with LBP's degree of anxiety, fear, and catastrophizing.